Considerations for method development and method translation in capillary liquid chromatography: A tutorial - Eliza K. Hanson; Samuel W. Foster; Christopher Piccolo; James P. Grinias (Journal of Chromatography Open)
HPLC remains one of the most widely used measurement techniques for chemical analysis. Capillary LC, which utilizes narrow diameter columns operated at lower flow rates than analytical-scale LC, continues to gain adoption based on its reduced mobile phase consumption and increased sensitivity when coupled to MS detection. This tutorial offers practical insights into the most critical aspects of translating analytical-scale separations to the capillary scale. The selection of pumping systems, detectors, and the potential for performance loss due to extra-column effects are examined within the context of separations using columns with inner diameters ≤ 0.3 mm. Column choices within this diameter range are also detailed, both in terms of stationary phase support options and general commercial availability. The impact of these various factors on the effective development/translation of LC methods down to flow rates under 10 µL/min is described to provide readers with a basis for implementing these strategies within their own analytical workflows.